81.7k views
18 votes
Guys please help me out ASAP, Due today. I

In an arithmetic sequence Sn = n² - 2n.
Use your formula in 2c to determine the value of
(a) T7 =
(b) Tn=

The formula in 2c : Sn - Sn-1 =Tn

User Bert H
by
5.4k points

1 Answer

10 votes

Answer:


T_7 = 11


T_n = 2n- 3

Explanation:

Given


S_n = n^2 -2n


T_n = S_n - S_(n-1)

Solving (a): T7

Substitute 7 for n in
T_n = S_n - S_(n-1)


T_7 = S_7 - S_(7-1)


T_7 = S_7 - S_6

Calculate S7 and S6


S_n = n^2 -2n


S_7 = 7^2 - 2 * 7 = 35


S_6 = 6^2 - 2 * 6 = 24

So:


T_7 = 35 -24


T_7 = 11

Solving (b): Tn


T_n = S_n - S_(n-1)

Where
S_n = n^2 -2n

Calculate
S_(n-1)

We have:


S_(n-1) =(n-1)^2 - 2(n-1)

Open brackets


S_(n-1) = n^2 -2n + 1 -2n +2


S_(n-1) = n^2 -2n-2n + 1 +2


S_(n-1) = n^2 -4n + 3

So:


T_n = S_n - S_(n-1)


T_n = n^2 - 2n - (n^2 -4n + 3)


T_n = n^2 - 2n - n^2 +4n - 3

Collect Like Terms


T_n = n^2 - n^2- 2n +4n - 3


T_n = 2n- 3

User Theodore Zographos
by
4.9k points